2022
DOI: 10.3390/ijms23158703
|View full text |Cite
|
Sign up to set email alerts
|

Four Cholesterol-Recognition Motifs in the Pore-Forming and Translocation Domains of Adenylate Cyclase Toxin Are Essential for Invasion of Eukaryotic Cells and Lysis of Erythrocytes

Abstract: Adenylate Cyclase Toxin (ACT or CyaA) is one of the important virulence factors secreted by Bordetella pertussis, the bacterium causative of whooping cough. ACT debilitates host defenses by production of unregulated levels of cAMP into the cell cytosol upon delivery of its N-terminal domain with adenylate cyclase activity (AC domain) and by forming pores in the plasma membrane of macrophages. Binding of soluble toxin monomers to the plasma membrane of target cells and conversion into membrane-integrated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In addition to this shared process of membrane disruption, LtxA and many of the RTX toxins possess a CRAC domain that enables strong binding to cholesterol. 47,[77][78][79][80][81] For this reason, we incorporated a large proportion of cholesterol in our liposomal formulation and observed that the incorporation of cholesterol in the liposomes greatly enhanced LtxA-mediated leakage. Prior work has used a similar approach, using natural or synthetic cell membranes to sequester toxins produced by Gram-positive bacteria due to their affinity for specific lipid components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this shared process of membrane disruption, LtxA and many of the RTX toxins possess a CRAC domain that enables strong binding to cholesterol. 47,[77][78][79][80][81] For this reason, we incorporated a large proportion of cholesterol in our liposomal formulation and observed that the incorporation of cholesterol in the liposomes greatly enhanced LtxA-mediated leakage. Prior work has used a similar approach, using natural or synthetic cell membranes to sequester toxins produced by Gram-positive bacteria due to their affinity for specific lipid components.…”
Section: Discussionmentioning
confidence: 99%
“…For a number of RTX toxins, it has been documented that the cholesterol dependence for the biological activity is sterol-specific, and it is due to direct toxin binding to the sterol molecules in the membrane and not to indirect effects of this lipid on the physical state of the phospholipid bilayer [ 69 , 79 , 100 , 108 ]. In 2014, Vazquez and colleagues, using different biochemical and biophysical assays, demonstrated the direct interaction of UPEC HlyA with cholesterol but not with sphingomyelin [ 100 ].…”
Section: Cholesterol Dependence Of the Cytolytic/cytotoxic Activity O...mentioning
confidence: 99%
“…Moreover, RtxA bound with 2–3-fold higher efficacy to the wells of an ELISA plate coated with cholesterol-BSA than to the wells coated with free BSA, showing that the toxin is able to interact with cholesterol independently of the presence of other membrane components [ 66 ]. Our group has recently shown that pre-incubation of B. pertussis CyaA with free cholesterol notably diminishes the toxin-induced hemolysis, and that binding of CyaA to pure lipid vesicles is notably increased proportionally to the cholesterol concentration present in the lipid bilayer (10–50%) and that ergosterol (ergosta-5,7,22-trien-3β-ol), an analog of cholesterol, cannot reproduce this effect [ 108 ].…”
Section: Cholesterol Dependence Of the Cytolytic/cytotoxic Activity O...mentioning
confidence: 99%
See 2 more Smart Citations